2022
DOI: 10.15620/cdc:118999
|View full text |Cite
|
Sign up to set email alerts
|

Provisional Life Expectancy Estimates for 2021

Abstract: This report presents life expectancy estimates calculated using complete period life tables based on provisional death counts for 2021 by sex and for the total, Hispanic, non-Hispanic American Indian or Alaska Native, non-Hispanic Asian, non-Hispanic Black, and non-Hispanic White populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
173
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(180 citation statements)
references
References 4 publications
6
173
0
1
Order By: Relevance
“…More distinctly, four [ 53 , 54 , 59 , 60 ] of the five studies with data on fatal overdoses showed increasing trends associated with the pandemic onset. These findings align with releases of national overdose deaths data showing a record of over 96,000 deaths in 2020 [ 63 ] and over 100,000 deaths in the 12 months up to May 2021 [ 64 ]. Such increases in negative overdose outcomes nationwide can potentially be explained when they are considered in conjunction with the aforementioned findings concerning potential increases in risky substance use behaviors, increases in the supply of fentanyl, and evidence of reduced harm reduction service capacities due to pandemic disruptions.…”
Section: Discussionsupporting
confidence: 86%
“…More distinctly, four [ 53 , 54 , 59 , 60 ] of the five studies with data on fatal overdoses showed increasing trends associated with the pandemic onset. These findings align with releases of national overdose deaths data showing a record of over 96,000 deaths in 2020 [ 63 ] and over 100,000 deaths in the 12 months up to May 2021 [ 64 ]. Such increases in negative overdose outcomes nationwide can potentially be explained when they are considered in conjunction with the aforementioned findings concerning potential increases in risky substance use behaviors, increases in the supply of fentanyl, and evidence of reduced harm reduction service capacities due to pandemic disruptions.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is confounding because CDC reports that African American and Hispanic people are 1.9 and 2.1 times, respectively, more likely than White people to die of COVID-19 ( 24 ). Yet, the “Hispanic paradox” ( 25 ) indicates that although older Hispanic people are not healthier than older non-Hispanic people, they have lower rates of mortality and the highest life expectancy in the US ( 26 ). Future research could examine this relationship more closely.…”
Section: Discussionmentioning
confidence: 99%
“…Varying definitions of CR exist across multiple disciplines, including disaster preparedness and planning in the face of climate change 15. Key elements that help communities bounce back after acute shocks are also indicators of a community's day-to-day vitality, cohesion, and social capital 16.…”
Section: Public Health Theory: Community Resiliencementioning
confidence: 99%